PENGARUH PROFESIONALISME DAN DISIPLIN SERTSA LINGKUNGAN KERJA TERHADAP PRODUKTIVITAS KERJA KARYAWAN PADA PT. KTC COAL MINING & ENERGY DI SAMARINDA - -, Hijriani Muharam (EKONOMIA, 2019)
The purpose of this study was to determine 1) the influence of professionalism on work productivity, 2) the influence of discipline on work productivity and, 3) the influence of the work environment on work productivity.Professionalism (X1) has a positive and significant effect on the work productivity of employees of PT KTC Coal Mining & Energy Samarinda. The theory used in this study is about Human Resource Management. Management is the science and art of planning, organizing, directing and supervising the efforts of the members of the organization in the use of organizational resources to achieve previously stated goals. Human Resource Management is a field of management that specializes in studying relationships and the role of humans in organizations.Analysis tools and hypothesis testing in this study use multiple regression analysis or multiple regression tools which consist of simultaneous test (simultaneous test) and partial test (each test). As for the data analysis process using the SPSS model 20 statistical tool.Work discipline (X2) has a positive and significant effect on the productivity of employees of PT KTC Coal Mining & Energy Samarinda. This is because there is an influence between the two variables, where the value of t count is greater than t table with the level of sig. 0.001 <0.05. This shows that there is a positive or significant influence or relationship between work discipline variables on work productivity.The work environment (X3) has a positive and significant effect on the work productivity of employees of PT. KTC Coal Mining & Energy Samarinda. This is because there is an influence between the two variables, where the value of t count is greater than t table with the level of sig. 0,000 <0,05. This shows that there is a positive or significant.